(untitled) (Revista de Ensino em Artes, Moda e Design, 2021)
This article is a summary of the Ph.D. thesis “Investigating parameters for analyzing equipment design as a social impact tool” held in 2020 at the Faculty of Fine Arts, University of Lisbon. It is a research that looks at the issues related to the design and its local dimension. We produced a synthesis description of these partnerships and we delimited (described and analyzed) the different relations to understand these experiences. Two stages divided the investigation. The first characterized a literature review. It involved approaches by different authors about the place of design and local production. We also discussed the approximations and differences between these two areas. It comprised the description and evaluation of 20 Brazilian and 5 Portuguese case studies. We conducted interviews from a semi-structured questionnaire that reached the artificer, the designer and the entities that foster these partnerships. The indicators used proved to be efficient in assessing the social, cultural, economic and territorial dimensions. The final considerations state that we are all artisans.